MUSLIM YOUTH AND PHILANTROPHIC ACTIVISM - Eja Armaz Hardi (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2021)
Since the last two decades, charity movements have been flourishing in Indonesian Islamic landscape. These organisations are involving not only state sponsored organizations, but also non-government associations and professional industries. This article exclusively discusses the youth-based charity movements in two important Islamic universities in Indonesia and tries to offer a new glance of youth charity movement as to which their movement relates to the issue of identity and social welfare. The article uses a qualitative method through a systematic literature review, in-depth interview, and observation to the activities of two youth-based charity movements at two state Islamic universities in Jambi and Surabaya. This paper further argues that the spirit of philanthropic movement does not only depend on economic wealth, but also on social solidarity, Islamic principle of economic distribution, and networks among the students that have been successfully translated into both social welfare activism and humanitarian activities.